Overspending on Online Game App Purchasing Among University Students in Sarawak, Malaysia - Parveen, Kaur; Arif, Jawaid; Armando, Nathaniel; Benita, Thomas; Muhamad, Zulfazid; Ricky, Kong (Siree Publications, 2020)
This research has sought to ascertain the pattern in-app purchasing in online games amongst university students. The sample consisted of 100 university students from all over the area of Kuching, Sarawak. This research revealed that out of the 100 students chosen, 91 were involved in in-app purchasing while 9 did not share the same passion. There are a wide range of factors as to why students are or are not involved in the habit of in-app purchasing in online games amongst university students. This research also studied on spending pattern of students, source of financial aid and factors contributing to reasons for in-app purchasing. While this study was conducted in Kuching, it has affected people from other regions as well, as there are many students who are not only involved in in-app purchasing, but addicted to it.